If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 19 + 3x = -17 + -3x + -20 Reorder the terms: 19 + x + 3x = -17 + -3x + -20 Combine like terms: x + 3x = 4x 19 + 4x = -17 + -3x + -20 Reorder the terms: 19 + 4x = -17 + -20 + -3x Combine like terms: -17 + -20 = -37 19 + 4x = -37 + -3x Solving 19 + 4x = -37 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 19 + 4x + 3x = -37 + -3x + 3x Combine like terms: 4x + 3x = 7x 19 + 7x = -37 + -3x + 3x Combine like terms: -3x + 3x = 0 19 + 7x = -37 + 0 19 + 7x = -37 Add '-19' to each side of the equation. 19 + -19 + 7x = -37 + -19 Combine like terms: 19 + -19 = 0 0 + 7x = -37 + -19 7x = -37 + -19 Combine like terms: -37 + -19 = -56 7x = -56 Divide each side by '7'. x = -8 Simplifying x = -8
| 5x=3x+54 | | x/9+7=14 | | -4=-y+2 | | 3x+2/5=x-1/3 | | -5k+2(k+2)=3k-38 | | 0.5log=50 | | (x/40)+(x/60) | | 5x-17+6=0 | | -3x-6=-4x | | 4x^2-20x-1=-1 | | (x/40)*(x/60) | | 2-4b=14 | | 2-4b=4 | | 1/8d-4+3/8-4+5 | | 5(r-3)-6=4r-4 | | 3(3c-1)-3=5c+2 | | -5/8*-5/8 | | 3x-11x+10=0 | | 12n+9m+3n-2m= | | (X+3)/6=(x+6)/5 | | 4x-9x-13=-5x+2-13 | | 2-5x-12=0 | | 98*5= | | 35+5.2y-1.2y=3 | | (4x-7)(2x+7)=0 | | 4(1+2p)=2+8p | | (3x-60)/5=60 | | -12.6*(-2)= | | (-5/7)=(x/98) | | 2x+2=4x+22 | | X-3x-10=0 | | 3(-2+4b)=42 |